ATROFIA PROGRESSIVA DE RETINA EM CÃO: RELATO DE CASO - Diaz, Felipe Garcia Zimer; dos Santos, Camila Alves; Thomé, Tainara; Guerra, Jéssyca; Wurfel, Simone de Fátima Rauber; de Lima, Jéssica Line Farias; Lusa, Tatiane (Anais de Medicina Veterinária, 2022)
.